Aqueous Speciation and Electrochemical Properties of a Water-Soluble Manganese Phthalocyanine Complex - Blakemore, James D. (2012)
The speciation behavior of a water-soluble manganese(III) tetrasulfonated phthalocyanine complex was investigated with UV-visible and electron paramagnetic resonance (EPR) spectroscopies, as well as cyclic voltammetry. Parallel-mode EPR (in dimethylformamide:pyridine solvent mix) reveals a six-line hyperfine signal, centered at a g-value of 8.8, for the manganese(III) monomer, characteristic of the d(4) S=2 system. The color of an aqueous solution containing the complex is dependent upon the pH of the solution; the phthalocyanine complex can exist as a water-bound monomer, a hydroxide-bound monomer, or an oxo-bridged dimer. Addition of coordinating bases such as borate or pyridine changes the speciation behavior by coordinating the manganese center. From the UV-visible spectra, complete speciation diagrams are plotted by global analysis of the pH-dependent UV-visible spectra, and a complete set of pK(a) values is obtained by fitting the data to a standard pK(a) model. Electrochemical studies reveal a pH-independent quasi-reversible oxidation event for the monomeric species, which likely involves oxidation of the organic ligand to the radical cation species. Adsorption of the phthalocyanine complex on the carbon working electrode was sometimes observed. The pK(a) values and electrochemistry data are discussed in the context of the development of mononuclear water-oxidation catalysts.